“The workload is staggering”: Changing working conditions of stay-at-home mothers under COVID-19 lockdowns - Aslam, Awish; Adams, Tracey L. (Gender, Work and Organization, 2022)
The COVID-19 pandemic has drawn attention to the home as a work environment, but the focus has centered on the experiences of paid workers. Stay-at-home mothers (SAHMs), for whom the home was already a workplace, have received little attention. This article explores how pandemic-induced lockdowns impacted SAHMs' working conditions and their experiences of childrearing. Combining a Marxist-feminist conceptualization of domestic labor with a labor process framework, we performed a qualitative content analysis of vignettes SAHMs shared about their day-to-day domestic labor in an online mothering community. Our findings show that, under lockdown conditions, the primacy given to partners' paid work combined with children's increased demands for care and attention reduced SAHMs work autonomy and exacerbated gender inequalities in the home. Combining labor process theory with literature on motherwork illuminates the home as a gendered work environment and enhances understanding of how changing conditions of domestic labor can intensify gender inequalities (and workers' awareness of them) that typically remain “hidden in the household.”. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; discipline; féminisme marxiste; féminisme matérialiste; inégalités; maternité; mères au foyer; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail de reproduction